Prevalence of electrocardiographic abnormalities in West-Asian and African male athletes. Issue 5 (19th May 2011) - Wilson, M G; Chatard, J C; Carre, F; Hamilton, B; Whyte, G P; Sharma, S; Chalabi, H
Abstract : Objectives: To evaluate the electrocardiographic (ECG) characteristics of West-Asian, black and Caucasian male athletes competing in Qatar using the 2010 recommendations for 12-lead ECG interpretation by the European Society of Cardiology (ESC). Design: Cardiovascular screening with resting 12-lead ECG analysis of 1220 national level athletes (800 West-Asian, 300 black and 120 Caucasian) and 135 West-Asian controls was performed. Results: Ten per cent of athletes presented with 'uncommon' ECG findings. Black African descent was an independent predictor of 'uncommon' ECG changes when compared with West-Asian and Caucasian athletes (p<0.001). Black athletes also demonstrated a significantly greater prevalence of lateral T-wave inversions than both West-Asian and Caucasian athletes (6.1% vs 1.6% and 0%, p<0.05). The rate of 'uncommon' ECG changes between West-Asian and Caucasian athletes was comparable (7.9% vs 5.8%, p>0.05). Seven athletes (0.6%) were identified with a disease associated with sudden death; this prevalence was two times higher in black athletes than in West-Asian athletes (1% vs 0.5%), and no cases were reported in Caucasian athletes and West-Asian controls. Eighteen West-Asian and black athletes were identified with repolarisation abnormalities suggestive of a cardiomyopathy, but ultimately, none were diagnosed with a cardiac disease. Conclusion: West-Asian and Caucasian athletes demonstrate comparable rates of ECG findings. Black African ethnicity is positively associated with increased frequencies of 'uncommon' ECG traits. Future work should examine the genetic mechanisms behind ECG and myocardial adaptations in athletes of diverse ethnicity, aiding in the clinical differentiation between physiological remodelling and potential cardiomyopathy or ion channel disorders.